TNF-Î± AND INTERLEUKIN-6 LEVELS IN CLINICAL EARLY ONSET NEONATAL SEPSIS TOWARD ACUTE LIVER INJURY - Dinarshanty, Diani; AS, Noorhamdani; Kawuryan, Siti Lintang; Wibowo, Satrio (Fakultas Kedokteran Universitas Brawijaya, 2017)
TNF-? and IL-6 level have an important role in acute liver injury during early onset neonatal sepsis. This study aims to investigate the correlation of TNF-? and IL-6 levels in neonates with clinical early onset neonatal sepsis toward the occurrence of acute liver injury 44 neonates with clinical early onset neonatal sepsis based on SIRS criteria and Rodwell hematologic scored ?3 were included in this study. Acute liver injury is defined as elevated of AST, ALT, or AST: ALT ratio <1. TNF-? and IL-6 levels were measured using ELISA methods. This study showed that TNF-? correlated significantly with AST level (p<0,001, r=0,570), ALT level (p<0,001, r=0,554), and AST: ALT ratio (p<0,001, r=0,652). This study also showed that IL-6 correlated significantly with AST level (p<0,001, r=0,523), ALT level (p<0,001, r=0,482), AST: ALT ratio (p<0,001, r=0,603). Regression test using backward methods showed that TNF-? influence acute liver injury (indicated by AST, ALT, and AST: ALT ratio) more than IL-6. We concluded that TNF-? and IL-6 level in clinical early onset neonatal sepsis correlated with acute liver injury, whereas early onset neonatal sepsis was correlated with acute liver injury.Keywords: Acute liver injury, clinical early neonatal sepsis, IL-6 level, TNF-? level